The Methodology of Implementing an Electronic Digital Signature System Based on a Virtual Infrastructure in the Information Systems of General Secondary Education Institutions - V. A. Gerasimov; M. A. Gerasimova; A. Р. Kuznezov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2025)
The article substantiates the feasibility of implementing an electronic digital signature system based on a virtual infrastructure in the general secondary education system as a means of digital transformation of this system and increasing the efficiency of educational processes. The article presents the results of the analysis of processes in the general secondary education system, during the implementation of which documents are signed. The article describes the technologies that make fault-tolerant and secure operation of such a system possible. A scheme for integrating an electronic digital signature system based on a virtual infrastructure into the information system of a general secondary education institution has been developed. The article identifies problematic issues that need to be resolved during the implementation and use of the scheme in the general secondary education system.